2019
DOI: 10.1051/e3sconf/201914003004
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual approaches for building a balanced portfolio of projects in oil and gas companies in exploration and production sector

Abstract: Uncertainties such as price volatility, supply and demand, global warming, technological progress, geopolitical situation, force the capital-intensive oil and gas sector to create a flexible portfolio of projects to proactively respond to changes. In an increasingly complex and uncertain environment, oil and gas companies around the world face continued pressure. It has become difficult to make strategic decisions and build long-term plans, so it has become vital to have a balanced portfolio. We suggest that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, it would be more efficient for the state economy if a large proportion of small businesses were conducted and opened in the production sector. Thus, the development of the country's industrial potential and more goods could be sold in domestic markets and through export channels in foreign markets (Molchanov and Romasheva, 2019;Bilgaev et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, it would be more efficient for the state economy if a large proportion of small businesses were conducted and opened in the production sector. Thus, the development of the country's industrial potential and more goods could be sold in domestic markets and through export channels in foreign markets (Molchanov and Romasheva, 2019;Bilgaev et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…An empirical classification framework for stock price prediction, given the previous day's price increase or decrease, facilitates this relationship by using random forests and decision trees. Molchanov and Romasheva [ 38 ]. In order to achieve the goals and maximize profitability, companies suggested that indicators should be created for a balanced portfolio, which would allow portfolios to be evaluated and current and potential projects ranked to create flexibility with minimal risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(a) elimination of economic obstacles to the development of marginal deposits, which will subsequently lead to an improvement in their economic situation and facilitate the attraction of PSC contractors to invest in hydrocarbon fields located in border territories, deep waters, or other areas associated with high costs and risks [65][66][67][68][69]. (b) elimination of obstacles to the development of oil and gas projects [70,71].…”
Section: Problems Solutionsmentioning
confidence: 99%